IJAR 2020
DOI: 10.36106/ijar/5620295
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Lidocaine 2%, Lidocaine 5% And Bupivacaine 0.5% in Transnasal Sphenopalatine Ganglion Block for the Treatment of Postdural Puncture Headache

Abstract: BACKGROUND: Postdural puncture headache (PDPH) is a complication commonly related to neuraxial anesthesia and dural puncture, with an incidence proportional to the diameter of the needle, ranging from 2% with a 29G to 10% with a 27G and 25% with a 25G. The development of ne gauge spinal needles and needle tip modication, has enabled a signicant reduction in the incidence of postdural puncture headache. PDPH presents as a dull throbbing pain with a frontal-occipital distribution. PDPH is thought to be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A retrospective study evaluating 386 SPG blocks for headache found no difference between bupivacaine and lidocaine for pain reduction [21]. A randomized controlled study of 90 patients compared SPG block with lidocaine 2%, lidocaine 5%, and bupivacaine 0.5% for treating post-dural puncture headache and again found no difference between the groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study evaluating 386 SPG blocks for headache found no difference between bupivacaine and lidocaine for pain reduction [21]. A randomized controlled study of 90 patients compared SPG block with lidocaine 2%, lidocaine 5%, and bupivacaine 0.5% for treating post-dural puncture headache and again found no difference between the groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…had also mentioned about no significant difference while comparing three local anesthetic drugs such as lidocaine 2%, lidocaine 5% and Bupivacaine 0.5% in their study. 3 Purva Kumrawat et al 10 mentioned in their study which was done in 18 parturients who underwent C-section under spinal anesthesia that SPGB is more effective than conservative management in the treatment of PDPH in the first 24 hrs. SPGB has faster onset of action versus conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The incidence and severity of PDPH varies according to the types, bores of needle and number of attempts. 3 The first response to PDPH in the clinical practice is conservative management which fails to show prompt result and it may take up to 7-10 days. However, The gold standard treatment for PDPH is an autologous epidural blood patch (AEBP), 4,5 which has its own set of advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%